Endoscopic ultrasound-guided drainage of pancreatic fluid collections with indeterminate adherence using temporary covered metal stents - Weilert, F.; Binmoeller, K. F.; Shah, J. N.; Bhat, Y. M.; Kane, S. (Endoscopy, 2012)
Transenteric drainage of a pancreatic fluid collection (PFC) with poor adherence to the bowel wall risks leakage and perforation. Elimination of tract dilation and the use of a fully covered self-expanding metal stent (FCSEMS) may improve safety. We evaluated endoscopic ultrasound (EUS)-guided drainage of PFCs using a one-step access device followed by placement of a FCSEMS. Eighteen patients (12 males; median age 50) with PFCs (median size 135 mm) meeting the criteria for indeterminate adherence were enrolled. After 7 – 10 days, the FCSEMSs were removed and exchanged for double-pigtail stents. When indicated, tract dilation and endoscopy-guided cyst debridement was performed. FCSEMS placement was technically successful in all patients without complications. Median procedure time was 37.5 minutes. Cystgastrostomy dilation resulted in dehiscence in one patient and was treated with repeat FCSEMS placement. Cyst resolution was achieved in 78 % of patients. FCSEMS placement without tract dilation enables safe initial drainage of PFCs with indeterminate adherence.